2021
DOI: 10.1021/acsami.1c01451
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Ultrafine Metal–Organic Framework Nanoparticles within Multichamber Carbon Spheres by a Two-Step Double-Solvent Strategy for High-Performance Catalysts

Abstract: Carbon-encapsulated metal–organic framework (MOF) composite is one kind of emerging new catalyst with high efficiency and has gained much attention. However, for this kind of composite catalyst, the key to improving its catalytic activity and durability is to realize the effective dispersion of MOF nanoparticles (NPs) and enhance the interaction between MOF NPs and the carbon matrix, which remain a significant challenge. Herein, ultrafine MOF NPs within multichamber carbon spheres (MOF@MCCS), for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Figure a–c shows TEM images (not full of a monolayer) of monodisperse Ni 0.8 Fe 0.2 alloy clusters prepared at deposition distances ( L ) of 537, 550, and 572 mm, respectively, and the sizes (insets of Figure a–c) were measured statistically by Nanomeasure software . It is shown that the average sizes of the clusters are 4, 5, and 6 nm, respectively.…”
Section: Experimental and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a–c shows TEM images (not full of a monolayer) of monodisperse Ni 0.8 Fe 0.2 alloy clusters prepared at deposition distances ( L ) of 537, 550, and 572 mm, respectively, and the sizes (insets of Figure a–c) were measured statistically by Nanomeasure software . It is shown that the average sizes of the clusters are 4, 5, and 6 nm, respectively.…”
Section: Experimental and Simulation Methodsmentioning
confidence: 99%
“…In fact, the simulation results are very consistent with the experiment, which will be discussed in detail. 15 It is shown that the average sizes of the clusters are 4, 5, and 6 nm, respectively. The standard deviations of them are as low as 0.5, 0.6, and 1.0 nm, respectively.…”
Section: Micromagnetic Simulationmentioning
confidence: 97%
“…10(a)) with higher catalytic activity, selectivity, durability, and recyclability by encapsulating ultrafine ZIF-67 NPs in multi-chamber carbon spheres (MCCS). 126 According to the scanning transmission electron microscopy (STEM) images, ZIF-67 NPs are not present on the material surface. The abundant carbon defects formed in the pyrolysis process endow the materials with higher catalytic performance.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…Beside the above vacuum method, the MOF precursor solution is also able to be encapsulated into the pores of the porous carbon material by using the double solvents method (DSM) [154]. For instance, Shen et al used a two-step DSM to introduce MOF precursor solutions into multichambered carbon spheres (MCCS) to form a series of MOF@MCCS composites (Fig.…”
Section: Three-dimensional Carbon and Mof Compositesmentioning
confidence: 99%